Breast cancer and mutation in the ataxia telangiectasia mutated gene: a case report - Bonilla Sepúlveda, Oscar Alejandro (2023)
Among women, breast cancer is the most common cancer in the world, accounting for 25.7 % of all cancers and thus making it a topic of interest in public health. Breast cancer is a complex, heterogeneous genetic disease and, in the vast majority of cases, of unknown etiology. Around 7 % of breast cancer cases in the general population present a susceptibility gene mutation of Mendelian inheritance. The ataxia telangiectasia mutated (ATM) gene mutation is found inless than 1 % of the general population, and association studies conducted with controls have shown that these alleles are characterized by a moderate risk (RR: 2 ‐ 4) for hereditary cancer. Mutations in ATM incompletely cosegregate the disease, with an estimated 15 % of mutation carriers in this gene developing cancer. The incomplete penetrance of ATM, as wellas other moderate‐risk genes, supports that they follow a polygenic model of cancer susceptibility. We report the case of a 35‐year‐old woman diagnosed with metachronous bilateral breast carcinoma—T4b N1 M0 stage IIIB left breast and T1c N0 stage I right breast, intrinsic luminal B subtype, HER2 overexpression and pathogenic variant of ATM gene c.7913 G>A, p. Trp2638*—who was treated with neoadjuvant chemotherapy, followed by mastectomy, sentinel node biopsy and radiotherapy. The objective of this case report is to describe the clinicopathological characteristics of breast cancer and its association with moderate‐risk gene mutations.